EXPLORATION OF POTENTIAL TOURIST ATTRACTIONS IN NAGARI TABEK PATAH - Rosalina, Linda; Susanti, Retnaningtyas; Yulastri, Asmar; Tasrif, Elfi; Komaini, Anton (PT. Hafasy Dwi Nawasena, 2023)
The tourism industry is currently one of the industries that plays an important role in national development in various countries. The tourism industry changes the lives of millions of people around the world by stimulating economic growth, creating jobs, reducing poverty, accelerating development and increasing tolerance. Nagari Tabek Patah is a nagari that has a lot of natural potential that can be used as a tourist attraction. If natural tourism can be managed properly, of course it can improve the local community's economy. The purpose of this study was to find out the potential and strategiesof the local community in developing tourism objects in Nagari Tabek Patah. The type of method in this study is a qualitative method with data collection techniques carried out by observation and interviews. From this research, it was found that there were several ways that the local community had done to develop tourist objects, including promotion by placing banners and creating social media accounts